A Neurospora crassa mutant which overaccumulates carotenoid pigments - R. W. Harding; D. Q. Philip; B. Z. Drozdowicz; N. P. Williams (Fungal Genetics Reports, 1984)
A Neurospora crassa mutant which overaccumulates carotenoid pigments